Answer:
=》Area = 180 sq.yd
Step-by-step explanation:
perimeter = 2l + 2b
where, we have l = 15
- so (2×15) + 2b = 54
- 30 + 2b = 54
- 2b = 24
- b = 12
now, Area = l × b = 12 × 15 = 180 sq.yd
Simplifying
9x + -3(x + 8) = 6x + -24
Reorder the terms:
9x + -3(8 + x) = 6x + -24
9x + (8 * -3 + x * -3) = 6x + -24
9x + (-24 + -3x) = 6x + -24
Reorder the terms:
-24 + 9x + -3x = 6x + -24
Combine like terms: 9x + -3x = 6x
-24 + 6x = 6x + -24
Reorder the terms:
-24 + 6x = -24 + 6x
Add '24' to each side of the equation.
-24 + 24 + 6x = -24 + 24 + 6x
Combine like terms: -24 + 24 = 0
0 + 6x = -24 + 24 + 6x
6x = -24 + 24 + 6x
Combine like terms: -24 + 24 = 0
6x = 0 + 6x
6x = 6x
Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 0
Solving
0 = 0
Answer:
- y = (x - 4)(x + 2i)(x - 2i)(x + √3)(x - √3) Possible answer
- y = (x - 4)(x^2 + 4)(x^2 - 3) Possible answer
Step-by-step explanation:
The simplest answer is that 2i cannot be a lone root. It must have a twin that is - 2i
√3 has the same sort of rule. It cannot be a root all by itself. It also must have a twin, in this case -√3
So the answer must be
(x - 4)(x + 2i)(x - 2i)(x + √3)(x - √3) <<< Possible answer
but this can be reduced even further.
- (x + 2i)(x - 2i) = x^2 - x*2i + x*2i - 4i^2
- (x + 2i)(x - 2i) = x^2 - 4(i)^2
- (x + 2i)(x - 2i) = x^2 + 4. Remember i^2 = - 1
By a similar method (x - √3)(x + √3) = x^2 - 3
So the polynomial is reduced to
(x - 4)(x^2 + 4)(x^2 - 3) <<<< Answer
If this is not among your answers and the factored form is not either, please tell me what is.
I am doing the same thing